Utilizing the Potential of Machine Learning and DataGoverned Techniques in Materials Science: From Materials Science to Medicine - Haydarov Hasanjon Hakimovich; Kushimov Bakhtiyor Alishovich (Periodica Journal, 2023)
This scientific article explores the use of the potential of machine learning and data-driven methods in materials science and its prospects in medicine. Various machine learning methods are analyzed that are used for a comprehensive analysis of material properties and their impact on the medical field. Examples of the application of machine learning in various areas of materials science, such as the analysis of the structure of materials, modeling of properties, and the development of new materials, are considered. The possibilities of using these methods to create new medical materials and improve the diagnosis and treatment of various diseases are discussed.
Keywords: learning; data management; materials science